Versatility of 7-Substituted Coumarin Molecules as Antimycobacterial Agents, Neuronal Enzyme Inhibitors and Neuroprotective Agents - Erika Kapp (Molecules, 2017)
A medium-throughput screen using Mycobacterium tuberculosis H37Rv was employed to screen an in-house library of structurally diverse compounds for antimycobacterial activity. In this initial screen, eleven 7-substituted coumarin derivatives with confirmed monoamine oxidase-B and cholinesterase inhibitory activities, demonstrated growth inhibition of more than 50% at 50 µM. This prompted further exploration of all the 7-substituted coumarins in our library. Four compounds showed promising MIC99 values of 8.31–29.70 µM and 44.15–57.17 µM on M. tuberculosis H37Rv in independent assays using GAST-Fe and 7H9+OADC media, respectively. These compounds were found to bind to albumin, which may explain the variations in MIC between the two assays. Preliminary data showed that they were able to maintain their activity in fluoroquinolone resistant mycobacteria. Structure-activity relationships indicated that structural modification on position 4 and/or 7 of the coumarin scaffold could direct the selectivity towards either the inhibition of neuronal enzymes or the antimycobacterial effect. Moderate cytotoxicities were observed for these compounds and slight selectivity towards mycobacteria was indicated. Further neuroprotective assays showed significant neuroprotection for selected compounds irrespective of their neuronal enzyme inhibitory properties. These coumarin molecules are thus interesting lead compounds that may provide insight into the design of new antimicrobacterial and neuroprotective agents.